PERAN PENDIDIKAN ISLAM DALAM MEMBENTUK KARAKTER INDIVIDU DAN MENGHADAPI PERUBAHAN SOSIAL DI ERA MODERNISASI - Naila Hanastasya Adzikry; Ihda Hayatunnisa; Rifani Alina Syamsi; Hisa Fakhriya; Nabilah Zalfa (STKIP Subang, 2026)
Islamic education plays a vital role in shaping one’s character and addressing the various social changes occurring in the era of modernization. The behavior and morals of the younger generation are greatly influenced by technological advancements, globalization, and shifts in society’s lifestyle. Although modernization offers many conveniences in various aspects of life, it also gives rise to various problems, such as a decline in moral values, an increase in individualistic attitudes, and the loss of religious values in daily life. In such a situation, Islamic education serves as a means to build one’s character, morals, and spirituality so that they can maintain their Islamic identity without losing it. This study employs a qualitative approach using literature review. Data was collected from various sources, including books, scientific journals, and academic articles on Islamic education, character development, social change, and modernization. This data was analyzed descriptively to understand the role of Islamic education in modern society.Research findings indicate that Islamic education instills moral values, discipline, responsibility, honesty, and spirituality, which shape a person’s character. In addition, Islamic educational institutions such as boarding school, madrasahs, Islamic schools, and non-formal educational institutions also play a vital role in imparting Islamic values to children. In the era of modernization, Islamic educational institutions must have the ability to adapt to advances in science and technology while continuing to uphold Islamic values. Therefore, to ensure that Islamic education remains relevant amid social changes in the modern era, innovation in teaching methods, strengthening character education, and the utilization of technology are necessary.